The Use of the School-Environment-Based Educational Game 'Language Detective' to Improve Vocabulary and Spelling Mastery Among Phase B Elementary School Students at Nania Christian Elementary School - Rumaruson, Fica Agralce; Koeswanti, Henny Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Limited vocabulary mastery and spelling proficiency in Indonesian remain challenges for elementary school students, largely due to teaching methods that tend to be teacher-centered, thereby limiting active student engagement. This study aims to describe the use of the school-environment-based educational game